Evaluation of hepatitis serology and frequency of viral reactivation in patients with inflammatory arthritis receiving biologic agents: a multicenter observational study - Capkin, Erhan; Yazici, Ali; Karkucak, Murat; Durmaz, Yunus; Toprak, Murat; Ataman, Sebnem; Yilmaz, Gurdal (Springer Heidelberg, 2023)
To evaluate of hepatitis serology and reactivation frequency in patients with rheumatic disease receiving biologic agents. Our study included patients with inflammatory rheumatic diseases from 23 centers, who were followed up with biological therapy. Demographic and clinical characteristics of the patients, duration of drug use and hepatitis serology and the state of viral reactivation were analyzed. A total of 4060 patients, 2095 being males, were included in our study. Of the patients, 2463 had Ankylosing Spondylitis (AS), 1154 had Rheumatoid Arthritis (RA), 325 had Psoriatic Arthritis (PsA), and 118 had other inflammatory rheumatic diseases. When the viral serology of the patients was evaluated, 79 patients (2%) who were identified as HBs Ag positive, 486 (12%) patients who were HBs Ag negative and anti-HBc IgG positive and 20 patients (0.5%) who were anti-HCV positive. When evaluated on a disease-by-disease basis, the rate of HBsAg was found to be 2.5% in RA, 2% in AS and 0.9% in PsA. Viral reactivation was detected in 13 patients while receiving biologic agents. HBs Ag was positive in nine patients with reactivation and negative in four patients. Anti-HBc IgG, however, was positive. Six of these patients had AS, four had RA, and three had PsA. The development of hepatitis reactivation in 11.4% of HBs Ag positive patients and 0.82% of anti-HBc IgG positive patients due to the use of biologic agents is an important problem for this group of patients. Antiviral prophylaxis is recommended to be started especially in patients who are HBs Ag positive and who are using biologic agents due to viral reactivation. Therefore, it is important to carry out hepatitis screenings before biologic agent treatment and to carefully evaluate the vaccination and prophylaxis requirements.
Keywords: Hepatitis; Inflammatory arthritis; Biologic agents; Viral reactivation